DIGITAL TRANSFORMATION OF TAX ADMINISTRATION AND ITS IMPACT ON ECONOMIC TRANSPARENCY: EVIDENCE FROM UZBEKISTAN (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This study investigates the theoretical and practical aspects of digital transformation in tax administration in Uzbekistan and evaluates its impact on economic transparency and fiscal sustainability. The research systematically analyzes the implementation of international tax standards, including OECD frameworks and BEPS initiatives, as well as the application of digital tools such as electronic invoicing, big data analytics, and risk-based tax monitoring systems. The findings indicate that digital transformation significantly enhances tax compliance, reduces the shadow economy, and improves administrative efficiency. However, persistent challenges remain in the areas of e-commerce taxation, transfer pricing regulation, and digital inequality across regions. The study provides scientifically grounded policy recommendations aimed at strengthening digital tax governance and ensuring sustainable economic development.